2022
DOI: 10.3389/fonc.2022.847957
|View full text |Cite
|
Sign up to set email alerts
|

The Studies of Prognostic Factors and the Genetic Polymorphism of Methylenetetrahydrofolate Reductase C667T in Thymic Epithelial Tumors

Abstract: ObjectiveTo describe the clinical features of a cohort of patients with thymic epithelial tumors (TETs) and to analyze their prognostic factors. In particular, we investigated the correlation between the genetic polymorphism of methylenetetrahydrofolate reductase (MTHFR) C667T and the incidence of TETs.MethodsPathological records were reviewed from the database of the Second Affiliated Hospital of Jiaxing University, from January 2010 to December 2020, and 84 patients with TETs were recruited for this study. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Moreover, this evidence was further corroborated by a recent investigation based on the TCGA database of TETs. The authors observed a negative correlation between MTHFR methylation and expression levels in TETs, and speculated that the lower activity of the MTHFR enzyme, also affected by the MTHFR C667T gene polymorphism, causes a significant DNA hypomethylation in TETs that promotes the activation of proto-oncogenes [108].…”
Section: Thymomasmentioning
confidence: 99%
“…Moreover, this evidence was further corroborated by a recent investigation based on the TCGA database of TETs. The authors observed a negative correlation between MTHFR methylation and expression levels in TETs, and speculated that the lower activity of the MTHFR enzyme, also affected by the MTHFR C667T gene polymorphism, causes a significant DNA hypomethylation in TETs that promotes the activation of proto-oncogenes [108].…”
Section: Thymomasmentioning
confidence: 99%
“…reveals an intriguing inverse correlation between MTHFR methylation and its corresponding expression levels in TETs. The authors speculate that the diminished activity of the MTHFR enzyme, influenced by the MTHFR C667T gene polymorphism, may contribute to significant DNA hypomethylation in TETs, thereby promoting the activation of crucial oncogenes ( 83 ).…”
Section: Epigenetic Modificationsmentioning
confidence: 99%